Students Who Orient towards Studying vs. Learning: Teachers' Perceptions - Rocío Quijano-López; Miguel Pérez-Ferra (MDPI AG, 2021)
Many present-day students orient towards outcomes instead of learning. This is leading to failure that affects students, families, the educational system itself, and occupational and financial systems in Spain. Indeed, current data points to an 18.2% university drop-out rate during the first year. The present study seeks to identify teachers' perceptions of the deficiencies pertaining to study orientations, their involvement in training processes, and student knowledge about the actual state of affairs regarding this topic. The target population for this incidental study was 1769 university lecturers, with a final participating sample of 317. A cross-sectional study was conducted, which was descriptive and inferential in nature. Linear regression was employed to explain variance. Outcomes showed a high degree of homogeneity in teachers' responses. Outcomes indicate that orientations towards academic learning and study are deemed necessary. Furthermore, such orientations do not prevail due to a lack of teacher engagement, possibly due to a lack of teacher training directed towards managing and balancing class time with monitoring practices. A degree of insufficiency was observed with regards to teacher training for study management, in addition to greater teacher engagement amongst hired teaching staff with indefinite contracts working at public or private institutions, relative to official permanent teaching staff.